Garrapatas (Acari: Ixodidae) asociadas a perros en diferentes ambientes de la provincia de Corrientes, Argentina - Debárbora, V.N. (2011)
Ticks (Acari: Ixodidae) of dogs in urban, peri-urban and rural areas from the Corrientes Province, Argentina, were studied. They were monthly collected during one year at 7 different sites. A total of 138 dogs were examined, and 87 (63.04%) of them were infested; and three species were determined: Amblyomma tigrinum (n=35), Amblyomma ovale (n=2) and Rhipicephalus sanguineus sensu lato (n=523). Both A. tigrinum and R. sanguineus s.l. had the highest prevalence in rural areas. Specimens of R. sanguineus s.l. were collected in the four seasons, but the peaks of abundance were detected in spring and summer. Amblyomma tigrinum was found in autumn, winter and spring, with the peak of abundance in spring, and the two specimens of A. ovale were collected in the spring. Rhipicephalus sanguineus s.l. and A. tigrinum were found in the three areas, but the former was always most tick abundant. Considering that the species of R. sanguineus complex are vectors of pathogens of dogs and humans, and due to the high prevalence detected in this study, it is evident that control methods of this tick should be applied at the areas included in this study.